Modeling the Thermal Performance for Different Types of Solar Chimney Power Plants - Ghassan F. Smaisim; Azher M. Abed; Ali Shamel (Complexity)
Nowadays, due to restrictions on fossil fuels, the use of renewable energies is increasing day by day. Among renewable energies, solar energy has received more attraction due to its availability in all places. Among solar energy technologies, the solar tower has been welcomed due to its high power generation of electrical energy. For accurate modeling of the studied system, each component of the system has been evaluated and modeling has been done. Therefore, in this research, solar tower modeling has been conducted to achieve high electrical energy production, and to better compare the production rate, 5 cities in Iran with different weather conditions have been considered. According to the results, it can be mentioned that the highest production power by the studied system is related to Shiraz city with an average production of 20 kW/m2, and among the cities studied, the lowest rate is related to Mashhad with a production power of 15 kW/m2.